2018
DOI: 10.1002/ab.21805
|View full text |Cite
|
Sign up to set email alerts
|

Ego depletion and the use of force: Investigating the effects of ego depletion on police officers’ intention to use force

Abstract: The current study aims to investigate corresponding self-control and self-control failures that are the result of ego depletion and its impact on police officers' decision to use force. For that purpose, a total of 200 German police recruits were randomly assigned to either an experimental or control group. Ego depletion was manipulated using the "e" crossing task. Participants then worked through a video-based scenario exercise, in which they encountered a provocative citizen. They were required to indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 67 publications
(112 reference statements)
0
17
0
Order By: Relevance
“…There is much to still understand about the use of force by police: From the law enforcement side, many questions remain regarding how these incidents happen. For example, is there an institutional issue, such as a training failure (see Lee et al, 2010), or are these incidents examples of an individual differences issue with regards to how certain officers manage high-stress encounters (e.g., Staller et al, 2019)? From the general public’s perspective, much remains misunderstood with regards to how police use of force is interpreted and judged.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is much to still understand about the use of force by police: From the law enforcement side, many questions remain regarding how these incidents happen. For example, is there an institutional issue, such as a training failure (see Lee et al, 2010), or are these incidents examples of an individual differences issue with regards to how certain officers manage high-stress encounters (e.g., Staller et al, 2019)? From the general public’s perspective, much remains misunderstood with regards to how police use of force is interpreted and judged.…”
Section: Discussionmentioning
confidence: 99%
“…After task completion, all cadets were put through a video-based scenario that involved an encounter with a belligerent citizen and were asked to indicate the point at which they would resort to using force against the citizen. Cadets in the ego-depletion condition indicated that they would use force earlier than those in the control condition, thus suggesting that circumstances that produce ego depletion of the officer in the field may lead to excessive or inappropriate use of force in an attempt to control the situation (Staller et al, 2019). From an organizational perspective, it has also been found that agencies that require supervisors or other higher-level personnel to fill out use of force incident forms report lower levels of use of force incidents than police departments that require the arresting officer to fill out the paperwork (Alpert & MacDonald, 2001).…”
Section: Academic Literature Addressing Police Use Of Forcementioning
confidence: 99%
See 2 more Smart Citations
“…With these mandates and the importance of discretion as a point of departure, the factors of conflict management and behavior play an important role. Notably, this is an area where officers have a breadth of possible approaches or behaviors ranging from the misuse of power to withdrawing from engaging in conflicts, and where a range of factors appear to affect the propensity of officers to use force (9,13,14). Notwithstanding the several investigations on different aspects of police work, less attention has been paid to the context of police education and how police officers are prepared for challenges they will meet in the line of duty.…”
Section: Introductionmentioning
confidence: 99%